Technological knowledge, product relatedness, and parent control: The effect on IJV survival - XU, Dean (Institutional Knowledge at Singapore Management University, 2007)
This article examines the relationships among parent firm technological knowledge, parent-IJV product relatedness, parent control over the IJV, and IJV survival. Combining the knowledge-based perspective and institutional theory, we argue that parent control itself does not necessarily lead to higher IN survival; it contributes to IN survival when the parent firm has a high level of technological knowledge, and when the IJV is product-related to this parent. Results obtained from 1038 Japanese IJVs based in China indicate that both equity control and managerial control of a Japanese parent had a positive interaction effect, with the parent's technological knowledge, on IN survival. Equity control also exhibited a positive interaction effect with product relatedness. In a sub-sample of 354 Sino-Japanese IJVs containing local parent information, managerial control by the Chinese parent was found to have a positive interaction effect, with Chinese parent-IN product relatedness, on IN survival.